2014
DOI: 10.1155/2014/253581
|View full text |Cite
|
Sign up to set email alerts
|

Potential Association between Breakfast Skipping and Concomitant Late-Night-Dinner Eating with Metabolic Syndrome and Proteinuria in the Japanese Population

Abstract: Skipping breakfast is considered to be an unhealthy eating habit linked to predispositions to obesity and type 2 diabetes. Because eating dinner late at night can elicit subsequent breakfast skipping, we investigated if skipping breakfast concomitant with late-night-dinner eating (LNDE) was associated with metabolic syndrome (MetS) and proteinuria in the general Japanese population. We examined self-reported habitual breakfast skipping and LNDE, MetS (modified ATP-III criteria), and proteinuria in a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 33 publications
(35 reference statements)
10
93
2
1
Order By: Relevance
“…However, even with the same meal contents, consuming in late-night-dinner lead to postprandial hyperglycemia [44]. Furthermore, it is reported that there is a significant correlation between skipping breakfast and late-night-dinner [48]. So, skipping breakfast might affect the result on this study.…”
Section: Discussionmentioning
confidence: 67%
“…However, even with the same meal contents, consuming in late-night-dinner lead to postprandial hyperglycemia [44]. Furthermore, it is reported that there is a significant correlation between skipping breakfast and late-night-dinner [48]. So, skipping breakfast might affect the result on this study.…”
Section: Discussionmentioning
confidence: 67%
“…The incidence of LEMs can be associated with that of SB the following morning because of several factors, such as a lack of time, impaired appetite and fatigue. Cross-sectional studies have shown that SB concomitant with LEMs was significantly associated with metabolic syndrome, and that hyperglycemia in the general Japanese population was associated with LEMs alone, but not SB alone 10,20 . Hence, the present study focused on the possible close association between SB and eating dinner late at night.…”
Section: Discussionmentioning
confidence: 99%
“…101 Additionally, the combination of late-night eating and skipping breakfast was associated with a greater risk of having the metabolic syndrome among Japanese adults (n=60 800; age, 20-75 years). 102 Compared with individuals with healthy eating patterns, those who ate late at night, defined as eating dinner within 2 hours of bedtime, and skipped breakfast had an OR for the metabolic syndrome of 1.17 (95% CI, 1.08-1.28). The associations of eating frequency and timing with inflammation and IR biomarkers were assessed in female participants in NHANES 2009 to 2010 (n=2212; mean age, 46.8 years).…”
Section: Meal Timing and Cardiometabolic Risk: Observational Findingsmentioning
confidence: 97%